Od pasji do dokumentacji. Czy kolekcjonerzy i archiwiści mogą się polubić? - Piętka-Hadała, Dorota (Archiwa – Kancelarie – Zbiory, 2011)
Od pasji do dokumentacji. Czy kolekcjonerzy i archiwiści mogą się polubić?